Diabetes with kidney injury may change the abundance and cargo of urinary extracellular vesicles - Gu, Dongfeng; Ding, Yanan; Jiang, Xin; Shen, Beili; Musante, Luca; Holthofer, Harry; Zou, Hequn (Frontiers in Endocrinology, 2023)
Background: Urinary extracellular vesicles (uEVs) are derived from epithelia facing the renal tubule lumen in the kidney and urogenital tract, may carry protein biomarkers of renal dysfunction and structural injury. However, there are scare studies focus on uEVs in diabetes with kidney injury. Materials and Methods: A community-based epidemiological survey was performed, and participants was randomized selected for our study. uEVs were enriched by dehydrated dialysis method, quantified by coomassie Bradford protein assay, and adjusted by urinary creatinine (UCr), then identified by transmission electron microscopy (TEM) nanoparticle track analysis (NTA) and western blot of tumor susceptibility gene 101 (TSG101). Results: Decent uEVs were got finally, with a homogeneous distribution, presenting a membrane-encapsulated structure like cup-shaped or roundish under TEM, having active Brownian motion, and presenting the main peak between 55 and 110 nm under NTA. Bradfrod protein assay show that the protein concentrations of uEVs were 0.02±0.02, 0.04±0.05, 0.05±0.04, 0.07±0.08, and 0.11±0.15 μg/mg●UCr separately, in normal controls, Prediabetes, diabetes with normal proteinuria, diabetes with microalbuminuria, and diabetes with macroproteinuria groups, after adjusting protein concentration with UCr by calculating the vesicles-to-creatinine ratio. Conclusions: Protein concentration of uEVs in diabetes with kidney injury increased significantly than normal controls before and after adjusted by UCr, therefore, diabetes with kidney injury may change the abundance and cargo of uEVs, which may be involved in the physiological and pathological changes of diabetes.